2015
DOI: 10.1002/bab.1288
|View full text |Cite
|
Sign up to set email alerts
|

Effect of acidic amino acids engineered into the active site cleft of Thermopolyspora flexuosa GH11 xylanase

Abstract: Thermopolyspora flexuosa GH11 xylanase (XYN11A) shows optimal activity at pH 6-7 and 75-80 °C. We studied how mutation to aspartic acid (N46D and V48D) in the vicinity of the catalytic acid/base affects the pH activity of highly thermophilic GH11 xylanase. Both mutations shifted the pH activity profile toward acidic pH. In general, the Km values were lower at pH 4-5 than at pH 6, and in line with this, the rate of hydrolysis of xylotetraose was slightly faster at pH 4 than at pH 6. The N46D mutation and also l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…In addition to these findings, the experiments showing the effect of surface and active site charges and hydrophobic side chains and their engineering (Nordwald and Kaar 2013;Burney et al 2015;Li and Turunen 2015;Nordwald et al 2015;Johnson and Snow 2017;Zhao et al 2018;Zhou et al 2019; Manna and Ghosh 2020) indicate many ways and positions in the protein structures to engineer properties that make the enzymes more tolerant to hydrophilic ILs.…”
Section: Improving Enzyme Performance In Ionic Liquidsmentioning
confidence: 95%
See 1 more Smart Citation
“…In addition to these findings, the experiments showing the effect of surface and active site charges and hydrophobic side chains and their engineering (Nordwald and Kaar 2013;Burney et al 2015;Li and Turunen 2015;Nordwald et al 2015;Johnson and Snow 2017;Zhao et al 2018;Zhou et al 2019; Manna and Ghosh 2020) indicate many ways and positions in the protein structures to engineer properties that make the enzymes more tolerant to hydrophilic ILs.…”
Section: Improving Enzyme Performance In Ionic Liquidsmentioning
confidence: 95%
“…Introduction of a negatively charged amino acid (aspartic acid) in the active site of the highly thermophilic GH11 xylanase from Thermopolyspora flexuosa, further decreased the activity in [EMIM]OAc compared to the wild-type enzyme. This was probably caused by the attraction of positively charged [EMIM] þ cation to the active site that leads to increased competitive inhibition of substrate binding by [EMIM]OAc (Li and Turunen 2015). While glycoside hydrolases have glutamic or aspartic acid side chains as catalytic residues, the molecular docking results showed that the highest energy cation binding sites in the active site are typically above the catalytic residues (Chawachart et al 2014;Hebal et al 2020).…”
Section: Enzyme-related Factors In Il Effectmentioning
confidence: 99%
“…Many endoxylanases from hyperthermophilic microorganisms show tolerance towards ILs [27,39,40,41]. In general, GH10 xylanases tolerate more 1-ethyl-3methylimidazolium acetate ([EMIM]OAc) and other ILs than GH11 xylanases [39,40,41,42]. However, resistance to protein unfolding in thermostable enzymes is not the only factor in IL tolerance [28,39,40].…”
Section: Introductionmentioning
confidence: 99%
“…However, there is a risk that the activity of xylanases could decrease, when the mutated sites on thermostability are located close to the active site canyon (Li and Turunen, 2014). In this study, in order to avoid site-directed mutagenesis on thermostability affecting the active site canyon, the active sites of xylanase XynZF-2 were predicted by PROSITE and verified by site-directed mutagenesis (E103D and E194D).…”
Section: Discussionmentioning
confidence: 99%